Study on the effect of wormseed plants; artemisia cina L. and chamomile; matricaria chamomilla L. on Growth Parameters and Immune Response of African Catfish, Clarias gariepinus - Abdelhadi, Yasser Mohamed; Saleh, Osama A.; Sakr, Saleh F. (2010)
A number of 420 fingerlings of catfish were used to examine the effect of wormseed plants and chamomile on the growth parameters and on non-specific immune response of the African catfish; Clarias gariepinus. Both types of herbs were used in rates of 1, 3 and 5% with 3 replicates per each of the 6 treatments. The 7th treatment was kept as a control group. The experimented catfish were fed with the 7 examined diets in the rate of 3% of fish biomass for 1 month. Different growth parameters as well as blood parameters were estimated to evaluate the growth performance and immune response of the experimented catfish. Results revealed that wormseed plants Artemisia cina L. in the rate of 3 and 5% and chamomile Matricaria chamomilla. L. in the rate of 1% showed the best figures of growth parameters as well as immune response parameters of the examined catfish.